An Overview of Green Chromatographic Analysis from Pharmaceutical Preparations - Doğan, Ayşegül; Eylem, Cemil C.; Akduman, Nursabah E. Başcı (Current Analytical Chemistry, 2021)
Background: Green Chemistry has emerged as a new field of study in chemistry in the past 15 years and is intended to be sustainable at the molecular level. Green Chemistry has focused on harmless chemical technologies to meet both environment and targets. The purpose of Green Chromatography is to protect the environment and the analyst like Green Chemistry. Objective: The main target is to reduce the consumption of hazardous solvent and to replacement of toxic and environmentally hazardous solvents with more benign alternatives. Methods: In addition, reducing the flow rate (decrease column interdiameter, etc.) in order to miniaturizing the waste generation is also within the field of green chromatography. On the other hand, the most effective technique for the “Green” approach can be miniaturized completely. Flow rate decreases from mL to microliter per minute. Thus, waste production and solvent consumption are significantly reduced. Recently, studies without organic solvents such as SFC, SBWC are frequently encountered. Results: Chromatographic analysis has the potential to become greener at all stages, from sample collection and preparation to separation and final determination. Liquid chromatography is often used in pharmaceutical analysis. Tons of wastes are produced every year for pharmaceutical analysis. For this reason, the greening approach in liquid chromatography becomes very important for human and environmental health in pharmaceutical analysis. Conclusion: This review discusses the approaches used to achieve the goals of green chromatography, aimed at protecting the environment and the analyst in pharmaceutical analysis. While one cannot completely convert the analysis to the green, the steps taken to green are very valuable, particularly in wide range used HPLC both in drug quality control laboratories in industry and in research studies.
Keywords: green solvents